The computed tomographic attenuation and the age of subdural hematomas. - Lee, K. S. (Korean Academy of Medical Sciences, 1997)
The sequential change in density (attenuation coefficient) of subdural hematomas (SDHs) in computed tomography (CT) is important in understanding the pathogenesis and evolution of SDHs. We retrospectively investigated the age of SDHs by CT in 446 cases. We included 30 cases of chronic SDHs, in whom the density was directly measured in the CT. The density of acute (within 7 days) SDH was hyperdense in 98.6%, isodense in 1.1%, and hypodense in 0.3% of the cases. In subacute (8-22 days) SDHs, it was hypodense in 45.7%, isodense in 42.9%, and hyperdense in 11.4%. In chronic (over 22 days) SDHs, 86.7% was isodense and only 13.3% was hypodense. In hypodense SDHs, 64.0% was the subacute, and 73.2% of the isodense SDHs was the chronic one. The mean interval from injury to CT was 0.5 +/- 1.6 days in hyperdense SDHs, 20.9 +/- 20.7 days in hypodense SDHs, and 54.9 +/- 44.0 days in isodense SDHs. In 30 cases of chronic SDH, the average density was 38.0 +/- 6.9 Hounsfield number(H) in 20 approximately 30 days, 43.8 +/- 12.8 H in 31 approximately 60 days, 51.8 +/- 5.1 H in 61 approximately 90 days, and 44.2 +/- 8.3 H in over 90 days. The density of acute SDH is usually hyperdense. It becomes hypodense within 3 weeks. Then the density progressively increases by the repeated microhemorrhage, which is the mechanism of enlargement of chronic SDH. The density of chronic SDH increases with time up to 90 days, then decreases again after maturation of the neomembrane, which is the mechanism of spontaneous resolution.